2013
DOI: 10.1128/jcm.01856-12
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Norovirus Infections in Asymptomatic Food Handlers in South Korea

Abstract: cPrevalence of asymptomatic norovirus infection was investigated in food handlers in South Korea. Among 6,441 subjects, 66 (1.02%) had norovirus infections confirmed by reverse transcription (RT)-PCR (real time and nested). GII-12 and GII-4 were the prevalent genotypes. Our data suggest that infection of asymptomatic food handlers is an important transmission source in norovirus outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 18 publications
2
15
1
Order By: Relevance
“…NoV surveillance faces several difficulties mainly associated with asymptomatic and prodromal shedding of the virus and chronic spread by some individuals, making it difficult to estimate correct prevalence based only on outbreak studies. Considering the total number of faecal samples collected and the lack of outbreaks, the NoV detection rate in this study (1.9%, 12 of 636) is similar to previous estimations of prevalence in asymptomatic individuals …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…NoV surveillance faces several difficulties mainly associated with asymptomatic and prodromal shedding of the virus and chronic spread by some individuals, making it difficult to estimate correct prevalence based only on outbreak studies. Considering the total number of faecal samples collected and the lack of outbreaks, the NoV detection rate in this study (1.9%, 12 of 636) is similar to previous estimations of prevalence in asymptomatic individuals …”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have identified that more than 90% of epidemic Considering the total number of faecal samples collected and the lack of outbreaks, the NoV detection rate in this study (1.9%, 12 of 636) is similar to previous estimations of prevalence in asymptomatic individuals. 45 In this study, all the successfully genotyped NoV strains (GI.3 and GII.6) were identified in diarrhoeal patients. Circulation of GI.3 was notified in Portugal since 2013, from an AGE outbreak in Portuguese military.…”
Section: Epidemiology Of Age Has Been Poorly Investigated In Portugalmentioning
confidence: 96%
“…Although NV GII.4 strains are widespread, they do not always cause AGE, which may account for the increased number of infections through asymptomatic transmission routes [26]. Furthermore, the population usually includes asymptomatic carriers of NV related to the occurrence of NV outbreaks [27]. Therefore, commonly occurring NV infections may result from multiple routes of transmission, especially for asymptomatic patients with NV pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A first factor is the low presumed 50% infectious dose (ID 50 ) of 18 segregated infectious NoV particles (Teunis et al, 2008). Other factors include the shedding of high amounts of virus particles (up to 10 10 virus particles per gram feces) (Jeong et al, 2013;Lai et al, 2012;La Rosa et al, 2009;Atmar et al, 2008;Ozawa et al, 2007;Lee et al, 2007;Chan et al, 2006), a high environmental stability Wang et al, 2013;Baert et al, 2009a) and the frequent occurrence of asymptomatic infections (Jeong et al, 2013;Nicolay et al, 2011;Phillips et al, 2010). Regarding HuNoV post-harvest contamination of foods, a recent study found that in 42.5% of described HuNoV food borne outbreaks between 2000 and 2008 an infected food handler was responsible (Baert et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%